2020
DOI: 10.3390/info11040194
|View full text |Cite
|
Sign up to set email alerts
|

A Situation Assessment Method with an Improved Fuzzy Deep Neural Network for Multiple UAVs

Abstract: To improve the intelligence and accuracy of the Situation Assessment (SA) in complex scenes, this work develops an improved fuzzy deep neural network approach to the situation assessment for multiple Unmanned Aerial Vehicle(UAV)s. Firstly, this work normalizes the scene data based on time series and use the normalized data as the input for an improved fuzzy deep neural network. Secondly, adaptive momentum and Elastic SGD (Elastic Stochastic Gradient Descent) are introduced into the training process of the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In addition, the authors of (Deng et al 2017 ) presented an FDNN for classification tasks, such as natural scene image categorization and stock trend prediction. Similar studies for image classification can be found in (Guan et al 2020 ; Kunchala et al 2020 ; Liu et al 2020a , b ; Liu et al 2020a , b ; Manchanda et al 2020 ; Tianyu and Xu 2020 ; Yeganejou and Dick 2018 , 2019 ; Yeganejou et al 2020 ; Zhang et al 2020a , b , c ).…”
Section: Analysis and Synthesis Of Datasupporting
confidence: 69%
See 3 more Smart Citations
“…In addition, the authors of (Deng et al 2017 ) presented an FDNN for classification tasks, such as natural scene image categorization and stock trend prediction. Similar studies for image classification can be found in (Guan et al 2020 ; Kunchala et al 2020 ; Liu et al 2020a , b ; Liu et al 2020a , b ; Manchanda et al 2020 ; Tianyu and Xu 2020 ; Yeganejou and Dick 2018 , 2019 ; Yeganejou et al 2020 ; Zhang et al 2020a , b , c ).…”
Section: Analysis and Synthesis Of Datasupporting
confidence: 69%
“…The study presented a hybrid diagnosis strategy (HDS) using fuzzy inference and a DNN to detect COVID-19 patients. Moreover, the novel hybrid approach to DNFS has been implemented for tumor and cancer detection and segmentation (Banerjee et al 2020 ; Lima et al 2020 ; Mudiyanselage et al 2020 ; Özyurt et al 2019 ; Pitchai et al 2020 ; Rahouma et al 2019 ; Sengan et al 2020 ; Shen et al 2020 ; Yang et al 2020 ; Zhang et al 2020a , b , c ).…”
Section: Analysis and Synthesis Of Datamentioning
confidence: 99%
See 2 more Smart Citations
“…By combining the analytic hierarchy process and fuzzy assessment, a fuzzy comprehensive assessment model was constructed for describing the degree of safety and integrating the effective data [24]. In [25], an improved fuzzy neural network-based situation assessment method was proposed for multiple vehicles, improving the intelligence and accuracy of assessments in a complex environment. However, the situation assessment research for cooperative hunting of multiple ASVs is still open for study.…”
mentioning
confidence: 99%